1999
DOI: 10.1161/01.hyp.34.4.943
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiotensin and Oxidative Stress in Essential Hypertension

Abstract: Abstract-In this review, we examine the possibility that small increments in angiotensin II are responsible for an increase in blood pressure and maintenance of hypertension through the stimulation of oxidative stress. A low dose of angiotensin II (2 to 10 ng ⅐ kg Ϫ1 ⅐ min Ϫ1 , which does not elicit an immediate pressor response), when given for 7 to 30 days by continuous intravenous infusion, can increase mean arterial pressure by 30 to 40 mm Hg. This slow pressor response to angiotensin is accompanied by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
223
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(238 citation statements)
references
References 74 publications
8
223
1
6
Order By: Relevance
“…We demonstrated that the renal excretion of 8-iso PGF 2␣ was increased in the mice infused with AngII400. This extends to the mouse the original observation of Romero et al in rat and swine that prolonged slow pressor infusion of AngII increased the plasma level of 8-iso PGF 2␣ (3). Tempol is a membrane permeant nitroxide that acts as an SOD mimetic.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We demonstrated that the renal excretion of 8-iso PGF 2␣ was increased in the mice infused with AngII400. This extends to the mouse the original observation of Romero et al in rat and swine that prolonged slow pressor infusion of AngII increased the plasma level of 8-iso PGF 2␣ (3). Tempol is a membrane permeant nitroxide that acts as an SOD mimetic.…”
Section: Discussionsupporting
confidence: 58%
“…The angiotensin II (AngII) slow pressor response is a gradually developing increase in BP (BP) with an initially subpressor rate of infusion (1)(2)(3)(4). The slow pressor response was first described in rats in 1963, (1) and subsequently has been demonstrated in rabbits, dogs and man (5).…”
mentioning
confidence: 99%
“…9 It has been shown that DNA damage contributes significantly to the development and progression of atherosclerosis. 10 Although increased levels of reactive oxygen species (ROS) 11,12 and decreased antioxidant capacity were investigated, the relationship between lymphocyte DNA damage and total antioxidant status (TAS) has not been investigated in both newly diagnosed and during therapy of essential hypertensive patients, so far.…”
Section: Introductionmentioning
confidence: 99%
“…1 Excessive production of reactive oxygen species (ROS), which outstrip antioxidant defence mechanisms, has been implicated in pathophysiological conditions that impact on the CV system. Hypertension is considered a state of oxidative stress (OX) that can contribute to the development of artherosclerosis 2 and other hypertension-induced organ damage. 3 Assessment of antioxidant activities and lipid peroxidation byproducts in hypertensives indicates an excessive amount of ROS and a reduction of antioxidant mechanism activity in blood, as well as in several other cellular systems, 4 including not only vascular wall cells, 5 but also those cells found in circulating blood.…”
Section: Introductionmentioning
confidence: 99%